Efficient 5′-3′ DNA end resection by HerA and NurA is essential for cell viability in the crenarchaeon Sulfolobus islandicus - Huang, Qihong (BMC Mol Biol, 2015)
BACKGROUND: ATPase/Helicases and nucleases play important roles in homologous recombination repair (HRR). Many of the mechanistic details relating to these enzymes and their function in this fundamental and complicated DNA repair process remain poorly understood in archaea. Here we employed Sulfolobus islandicus, a hyperthermophilic archaeon, as a model to investigate the in vivo functions of the ATPase/helicase HerA, the nuclease NurA, and their associated proteins Mre11 and Rad50. RESULTS: We revealed that each of the four genes in the same operon, mre11, rad50, herA, and nurA, are essential for cell viability by a mutant propagation assay. A genetic complementation assay with mutant proteins was combined with biochemical characterization demonstrating that the ATPase activity of HerA, the interaction between HerA and NurA, and the efficient 5′-3′ DNA end resection activity of the HerA-NurA complex are essential for cell viability. NurA and two other putative HRR proteins: a PIN (PilT N-terminal)-domain containing ATPase and the Holliday junction resolvase Hjc, were co-purified with a chromosomally encoded N-His-HerA in vivo. The interactions of HerA with the ATPase and Hjc were further confirmed by in vitro pull down. CONCLUSION: Efficient 5′-3′ DNA end resection activity of the HerA-NurA complex contributes to necessity of HerA and NurA in Sulfolobus, which is crucial to yield a 3′-overhang in HRR. HerA may have additional binding partners in cells besides NurA. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12867-015-0030-z) contains supplementary material, which is available to authorized users.